Principles for sustainable public open spaces in Sandton: a recommendation for the Johannesburg Metropolitan Open Space System (JMOSS) - Shelton, Ingrid (My University, 2016)
Public open spaces such as parks provide vibrancy to the ordinary city by means of providing spaces for the community for recreational, health and leisure activities. A sustainable public open space provides an opportunity for a city to become more sustainable where a public open space is more than a space for the community. This research aims at developing a set of principles that may be adopted by the Johannesburg Metropolitan Open Space System (JMOSS) in order to create sustainable public open spaces. The objectives of the research report include unpacking various debates regarding the use, users and definition of public open spaces, identifying what the existing principles are for open spaces as used by JMOSS, identifying where the parks and vacant parcels of land are in the Sandton and surrounding area, identifying what makes a public open space coherent, contextual and co-existent, identifying the shortfalls of the public open spaces in Sandton in terms of their coherency, co-existence, contextuality and sustainability, and identifying local and international precedents of Sustainable Public Open Spaces. The nature of this research report will include qualitative research where in depth interviews, photographs, mapping and case studies will be used in order to develop the principles for sustainable public open spaces. Two main concepts will be drawn on to develop the principles for sustainable public open spaces. Firstly, the concept of sustainable public open spaces by Reiter (2004) whereby the three principles of coherence, co-existence and contextuality are used. Secondly, the concept of sustainability as discussed by Gedikli (n.d.) where sustainable urban development incorporates social justice, sustainable economies, and environmental sustainability. Therefore, the concept of sustainability is the focus of how public open spaces can become more resilient, adaptable, efficient and effective spaces within the city for the public to use, by developing a set of principles for sustainable public open spaces. This research report culminates in the development of a set of principles for sustainable public open spaces, entitled “The Three Cs for Sustainable Public Open Spaces”. These principles can be applied on a generic scale but require guidelines in the context in which they are applied. Therefore, these principles are derived alongside guidelines for the context of the public open spaces within and around the Sandton CBD.
A Research Report submitted in fulfilment of the requirements for the degree in Master of Science in Town and Regional Planning, University of the Witwatersrand, 2016
Keywords: City planning--South Africa--Sandton; Open spaces--South Africa--Sandton; Environmental management--South Africa--Johannesburg; Metropolitan areas--South Africa--Johannesburg